Radio-frequency identification: A cost effective tool to improve livestock sector - RUHIL, A P; MOHANTY, T K; RAO, S V N; LATHWAL, S S; SUBRAMANIAN, V VENKATA (The Indian Journal of Animal Sciences, 2013)
Animal identification has become necessary now-a-days in livestock management at global level due to outbreak of animal diseases like bovine spongiform encephalopathy (BSE) commonly known as mad cow disease, FMD and swine flu. Unique identification and tracking of livestock help in providing rapid and precise information about animals to take prompt action in controlling disease outbreak, ensuring quality livestock products for public health, mitigating the false insurance claims etc. In modern age, one of the important contributions of ICT in livestock sector is development of electronic tags for unique identification of animals by using RFID (radio-frequency identification) chips, which are cheap, unique and tamperproof. Through a magnetic reader one can get information about the animal, which includes date of birth, breed, milk yield, owner etc. Automatic identification of individual animal helps in improving the farm management practice and welfare of animals. Although RFID is being very widely used in many of the organised farms because of its unique advantages, it is not being recommended by any government agency. Once this chip (grain size) is implanted in the animal one can identify this animal anywhere in the country, thus reducing malpractices in the implementation of many government schemes.